2008
DOI: 10.2337/dc07-2248
|View full text |Cite
|
Sign up to set email alerts
|

Ser1369Ala Variant in Sulfonylurea Receptor Gene ABCC8 Is Associated With Antidiabetic Efficacy of Gliclazide in Chinese Type 2 Diabetic Patients

Abstract: OBJECTIVE -The purpose of this study was to investigate whether genetic variants could influence the antidiabetic efficacy of gliclazide in type 2 diabetic patients. RESEARCH DESIGN AND METHODS-A total of 1,268 type 2 diabetic patients whose diabetes was diagnosed within the past 5 years and who had no recent hypoglycemic treatment were enrolled from 23 hospitals in China. All of the patients were treated with gliclazide for 8 weeks. Fasting and oral glucose tolerance test 2-h plasma glucose, fasting insulin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 22 publications
9
96
2
3
Order By: Relevance
“…Our results also indicated that the current BMI of patients with TPP was higher than that of patients with pure hyperthyroidism, confirming the results of Soonthornpun et al (2009). Additionally, a Chinese study revealed that non-obese type 2 diabetic patients with the Ala1369 variant have a better hypoglycaemic response to anti-diabetic sulphonylurea drug gliclazide than Ser1369 patients, reinforcing the existence of insulinresponse genetic predisposition for those bearing this variant (Feng et al 2008). In this study, the C-allele of the Ala1369 risk variant was present at a higher frequency in TPP patients than in the population genetics control that consisted of 1092 multi-ethnic subjects from the 1000 Genomes project.…”
Section: Discussionsupporting
confidence: 85%
“…Our results also indicated that the current BMI of patients with TPP was higher than that of patients with pure hyperthyroidism, confirming the results of Soonthornpun et al (2009). Additionally, a Chinese study revealed that non-obese type 2 diabetic patients with the Ala1369 variant have a better hypoglycaemic response to anti-diabetic sulphonylurea drug gliclazide than Ser1369 patients, reinforcing the existence of insulinresponse genetic predisposition for those bearing this variant (Feng et al 2008). In this study, the C-allele of the Ala1369 risk variant was present at a higher frequency in TPP patients than in the population genetics control that consisted of 1092 multi-ethnic subjects from the 1000 Genomes project.…”
Section: Discussionsupporting
confidence: 85%
“…A recent publication reported genotyped 25 SNPs from 661 Chinese T2DM patients who received 8 weeks of gliclazide therapy. The subjects with GG genotype in SUR exon 33(S1369A, rs757110) had a 7.7% greater decrease in FPG and 11.9% greater decrease in HbA1c after 8 weeks of gliclazide therapy [127].…”
Section: Sulfonylurea Receptormentioning
confidence: 98%
“…It was described that the exon 33 of the ABCC8 (rs757110) and KCNJ11 (rs5210) genes were associated with gliclazide antidiabetic efficacy [127]. SNPs of TCF7L2 had been consistently associated with T2DM in different ethnic descent and also had great impact on the T2DM patients' response to sulfonylureas [128].…”
Section: Othersmentioning
confidence: 99%
“…Isoleucine is usually interchangeable with leucine and occasionally with valine in proteins. Of 13 studies on DM, 3 showed strong associations between this variant and T2DM 38,41,46 , whereas the remaining studies showed no association with T2DM47 [60][61][62][77][78][79][80][81][82] . In another study, the rs5215 polymorphism was associated with blood pressure among subjects with T2DM 47,93 .…”
Section: Rs5215mentioning
confidence: 99%